Perancangan Media Pembelajaran Informatika Menggunakan Powtoon Di SMPN 2 Bukittinggi - Rizky Handayani Pasaribu; Hari Antoni Musril; Riri Okra; Sarwo Derta; Ryan Amanda (J-INTECH ( Journal of Information and Technology), 2023)
Informatics learning in class VII at SMPN 2 Bukittinggi experiences problems, namely students feel bored and waste time because they write too much material. so learning media such as learning videos are needed. This video was developed using powtoon. The research method used is Research and development (R&D) with the Planning, Production, Evaluation (PPE) development model. The results of this research produced a product in the form of a learning video created using Powtoon and accessed via the Linktree platform. The product test results show that the validity test involving 5 experts produced a score of 0.80 in the "valid" category. The practicality test involving 3 respondents produced a score of 0.94 in the "very high" category. The effectiveness test involving 1 teacher and 28 students produced a score of 0.86 in the "high effectiveness" category. This shows that learning video products created using Powtoon and distributed via Linktree are considered to have high validity, practicality and effectiveness in the learning process.